Al-Madunat wa Syawty wa Tatbiquha fi Tarqiyatil Maharati Lughah ‘Arabiyah - Isnol Khotimah; Firda Aprilia Yutami; Kholifah (Lisan An Nathiq : Jurnal Bahasa dan Pendidikan Bahasa Arab, 2021)
This study aims to describe the benefits of blogs and spotify that can be used in developing Arabic language skills by expressing ideas or ideas in written form in Arabic so that they can improve skills reading and writing. Besides that, Spotify can also be used as a learning media which can improve students' listening skills. This research uses a qualitative method with a practical approach to improve reading & writing skills of PBA students at Nurul Jadid Paiton University. Various data collection techniques such as open interviews about the experience of using blogs & sporty, observing student reactions to the benefits of blogs & sporty in Arabic & students practicing fun drills. Then the collected data is analyzed inductively where the researcher parses, sorts out the main ones, interprets the data sequentially and finally becomes a complete & detailed conclusion. Research findings show that blogs can effectively improve students' writing and reading skills. By doing easy things such as writing a diary on a regular basis, it will increase vocabulary that can be used in Arabic so that gradually you will be able to write according to standard Arabic rules. Besides that, blogs can also improve reading skills, while spotify can improve listening skills, Arabic messages (simple conversation podcasts) are conveyed easily & attractively to listeners (mustami').